Literasi Digital dan Implikasinya terhadap Pemahaman Fikih Ibadah Mahasiswa PAI di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) - St. Najma (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
Abstract This study aims to analyze the level of digital literacy among students of the Islamic Religious Education (PAI) study program at State Islamic Higher Education Institutions (PTKIN) and its implications for the quality of their understanding of fiqh al-ibadah. Employing a descriptive qualitative approach with data collection techniques comprising comprehensive literature study and analysis of student digital behavior trends, this research identifies two poles interacting dynamically: on one hand, the expansion of access to religious content through digital platforms has opened unprecedented opportunities for democratizing Islamic jurisprudence knowledge; on the other, the tendency toward instant content consumption potentially reduces depth of understanding of ijtihad methodology and classical fiqh epistemology. Findings indicate that PAI students generally possess adequate technical digital skills, yet remain weak in the critical literacy dimension namely the ability to evaluate the validity, authority, and religious context of digital sources. This phenomenon produces a literacy paradox: students who appear "digitally literate" operationally are paradoxically vulnerable to fragmented and superficial fiqh understanding. This study recommends integrating critical digital literacy education into the PAI curriculum at PTKIN  not as an elective add-on, but as a core competency embedded inseparably within the broader process of fiqh learning. Only through this approach can PAI students leverage digital platforms optimally as tools that strengthen, rather than replace, the structured and methodological tradition of Islamic scholarship